Causes and consequences of failure to file the annual return by the tax payer: A case study of Shinyanga municipality - Samwel, Frank (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfilment of the requirement for the award of Master’s Degree of Laws in Commercial Law (LL.M. CM.) of Mzumbe University